Clinical Impacts of ST- Segment Non-Resolution after Thrombolysis for Myocardial Infarction - Islam, Syed Aminul; Faruque, Md; Rahman, Fazlur; Hoque, Harisul; Fatema, Nilufar (University Heart Journal, 2019)
Streptokinase therapy for acute myocardial infarction reduces early mortality and improves outcomes. Failure of reperfusion after streptokinase therapy for acute myocardial infarction is common and indicates a poor prognosis. We investigated the clinical consequences of non-resolution of the ST segment after thrombolytic therapy for acute ST-elevation myocardial infarction, in 80 consecutive patients admitted to a coronary care unit. Failed thrombolysis was defined as <50% ST-segment resolution at 90 minutes after the start of thrombolytic treatment. Outcomes were measured in terms of in hospital adverse events and mortality at 6 weeks. Thrombolysis was successful, in terms of ST-segment resolution, in 59 patients (73.75%). After adjustment for other factors, ST resolution was the only independent predictor of an uncomplicated recovery in hospital. ST-segment resolution is a useful marker of successful thrombolysis and relates to clinical outcome. Average hospital stay was 2 days greater in non resolved ST-segment group than in ST-segment resolved group. At 6 weeks overall early mortality was much lower in the ST segment resolution group (1.7% versus 57.1% with P value of <0.001). So, non resolution of ST-segment in electrocardiogram following thrombolytic therapy in acute STEMI has paramount importance. If assessed routinely it might assist, along with other clinical markers, in the identification of high risk patients. University Heart Journal Vol. 15, No. 1, Jan 2019; 3-7